Nickel-based electrocatalyst as well as preparation method and application thereof

By depositing a nickel-based alloy film on nickel foam and loading Ru particles, a nickel-based electrocatalyst was prepared, which solved the problems of slow kinetics and high overpotential of the existing alkaline water electrolysis hydrogen reaction catalyst, and achieved efficient and low-cost electrolytic hydrogen production.

CN119800419AActive Publication Date: 2025-04-11TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510285326.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-04-11
Estimated Expiration
2045-03-11

AI Technical Summary

Technical Problem

The existing alkaline water electrolytic hydrogen reaction catalysts are slow in kinetics and have high overpotentials, making it difficult to achieve efficient and low-cost electrolytic hydrogen production.

Method used

Using nickel foam as the base material, a nickel-based alloy film was deposited by magnetron sputtering method, and Ru particles were loaded by liquid phase reduction method to prepare a nickel-based electrocatalyst.

Benefits of technology

It realizes long-term and stable operation of driving large current density at low potential, with excellent alkaline high current hydrogen evolution performance and good durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800419A_ABST
    Figure CN119800419A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of hydrogen evolution electrocatalyst preparation, and particularly relates to a nickel-based electrocatalyst and a preparation method and application thereof. According to the nickel-based electrocatalyst, foamed nickel serves as a substrate material, a nickel-based alloy film is obtained through a direct-current magnetron sputtering method, and then the nickel-based electrocatalyst is obtained through liquid-phase reduction treatment of ruthenium. The invention provides a design thought of a hydrogen evolution electrocatalyst which is low in cost, easy to obtain and high in activity, and the nickel-based electrocatalyst prepared by the method has relatively high charge transfer efficiency and excellent hydrogen evolution activity, and shows good durability and relatively low hydrogen evolution overpotential under a long-term alkaline large-current condition. The preparation method disclosed by the invention can be used for synthesizing different nickel-based alloy pre-catalysts, and has a wide development prospect and a relatively large application space.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electrocatalytic material, belonging to the technical field of hydrogen evolution electrocatalyst preparation, and in particular to a nickel-based electrocatalyst and a preparation method and application thereof. Background Art

[0002] Hydrogen is non-toxic, odorless, clean and pollution-free, and has a high calorific value (142MJ / kg), which is about three times more than petroleum. It is an ideal substitute for fossil fuels. In the future, hydrogen energy will play a key role in the transformation from fossil energy to clean energy. Hydrogen is taken from water and generates water after combustion. It can be recycled to achieve zero pollution and zero emission. At present, there are several ways to produce hydrogen: hydrogen from fossil fuels, recovery of hydrogen by-products from hydrogen-containing tail gas, and hydrogen production by electrolysis of water. Hydrogen production by electrolysis of water accounts for only a small part. Hydrogen production by fossil fuels and recovery of hydrogen by-products from hydrogen-containing tail gas account for about 96% of hydrogen production. This process consumes a lot of fossil energy and emits excessive carbon dioxide, which is contrary to the country's dual carbon goals. Hydrogen production by electrolysis of water has no carbon emissions, avoids greenhouse gas emissions of methane in the steam reforming process, complies with the principle of sustainable development, and is the trend of hydrogen production. Alkaline water electrolysis has received widespread attention due to its low equipment requirements and its ability to effectively avoid acid mist and corrosion. However, in alkaline media, the additional water dissociation step leads to sluggish kinetics. To overcome the sluggish kinetics and minimize the overpotential of the hydrogen evolution reaction, it is urgent to design alkaline HER catalysts with high activity, high stability, and durability.

[0003] In current research, Pt-based catalysts are widely used because of their suitable hydrogen adsorption free energy, but their cost is high, while Ru-based catalysts are low in cost and have similar Ru-H bond strength to Pt, and are considered to be ideal substitutes for Pt-based catalysts. However, Ru-based catalysts also have certain disadvantages, such as poor water dissociation ability, resulting in insufficient proton supply; excessively strong Ru-H bond strength makes H* intermediates adsorbed strongly, hindering H2 desorption. Therefore, a series of studies are devoted to combining Ru with suitable transition metal-based carriers, optimizing Ru-H adsorption energy and improving water dissociation ability through electronic regulation and other means. In current research, nickel-based catalysts have attracted widespread attention because of their high conductivity and good water molecule adsorption / desorption performance. Alloying them with other transition metals can improve the intrinsic electrocatalytic activity and corrosion resistance of the catalyst, and can also optimize the hydrogen adsorption free energy by adjusting the electronic structure of the active site, which is conducive to the development of high current density hydrogen evolution and efficient and low-cost water electrolysis hydrogen production technology. Summary of the invention

[0004] The present invention overcomes the deficiencies of the prior art and provides a nickel-based electrocatalyst to meet the research and application needs in the field.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a nickel-based electrocatalyst, using foamed nickel as the base material, a layer of nickel-based alloy film is deposited on the surface of the foamed nickel by a magnetron sputtering method, and then the nickel-based electrocatalyst is obtained by a liquid phase reduction method.

[0006] The present invention also provides a method for preparing the above nickel-based electrocatalyst, comprising the following steps: (1) A nickel-based alloy film was deposited on nickel foam by DC magnetron sputtering: first, the target material was installed and the treated nickel foam was fixed in the sample area. During the deposition process, the working atmosphere was argon and the pressure was selected according to different transition metals. Before the formal deposition, the nickel target and the different transition metal targets were pre-sputtered in an argon atmosphere for five minutes to remove the surface oxide layer. Then, the deposition power of nickel was adjusted to 50 W and the deposition power of other transition metals was adjusted to 20 W. The deposition was carried out for 30 minutes on both sides to obtain a nickel-based alloy pre-catalyst. (2) The nickel-based alloy precatalyst obtained in step (1) is immersed in a ruthenium trichloride solution, and then reduced with a sodium borohydride solution. The ruthenium attached to the surface of the nickel foam is then washed away with deionized water, washed with ethanol, and dried to obtain a nickel-based electrocatalyst.

[0007] As a further limitation of the technical solution of the present invention, the purity of the argon gas in step (1) is 99.999% and the flow rate is 30 sccm.

[0008] As a further limitation of the technical solution of the present invention, in step (1), the pre-sputtering power of the nickel target and the different transition metal targets is 70W.

[0009] As a further limitation of the technical solution of the present invention, the transition metal target in step (1) is cobalt, molybdenum, copper, tin or zinc. Except for the molybdenum target having a purity of 99.95%, the purity of the other targets is 99.999%.

[0010] As a further limitation of the technical solution of the present invention, the pressures corresponding to the cobalt, molybdenum, copper, tin and zinc in step (1) are 0.5Pa, 0.7Pa, 0.7Pa, 0.7Pa and 0.8Pa respectively.

[0011] As a further limitation of the technical solution of the present invention, the size of the nickel foam in step (1) is 1*1.2cm -2 In step (2), the ruthenium trichloride solution is a 20 mL aqueous solution containing 25 mg of RuCl3•xH2O, and the immersion time is two hours.

[0012] As a further limitation of the technical solution of the present invention, the concentration of the sodium borohydride solution is 0.5 mol / L, and the volume ratio of the used ruthenium trichloride solution to the sodium borohydride solution is 2:1.

[0013] As a further limitation of the technical solution of the present invention, the drying condition of step (2) is drying in an oven at 110° C. for three hours.

[0014] In addition, the present invention also provides the use of the above-mentioned nickel-based electrocatalyst in the cathode hydrogen evolution reaction at an alkaline high current density. The nickel-based electrocatalyst prepared by the method of the present invention has excellent hydrogen evolution activity and exhibits good durability and low hydrogen evolution overpotential under long-term alkaline high current conditions.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The nickel-based alloy precatalyst of the present invention is in the form of a thin film, and has a closely arranged columnar structure in cross section, which is firmly connected to the nickel foam and can be used as an excellent carrier of the nickel-based electrocatalyst. Different nickel-based alloy precatalysts can be obtained by depositing the nickel target and other transition metal targets simultaneously in a DC magnetron sputtering system.

[0016] 2. The Ru particles are loaded on the nickel-based alloy pre-catalyst by liquid phase reduction method, which retains the dense film structure of the nickel-based alloy pre-catalyst. At the same time, the film structure can make the Ru particles evenly distributed, so that the catalyst has abundant active sites and high intrinsic activity. The interface between the Ru particles and the nickel-based alloy film is conducive to charge transfer, thereby realizing electron redistribution.

[0017] 3. The nickel-based electrocatalyst described in the present invention has excellent alkaline large current hydrogen evolution performance and can drive long-term stable operation at a large current density at a relatively low potential.

[0018] 4. The nickel-based electrocatalyst described in the present invention is easy to prepare, has a simple process, and is easy to realize mass production.

[0019] The invention has reasonable design, can prepare different nickel-based alloy electrocatalysts, and has broad development prospects and large application space. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a scanning electron microscope image of NiCo obtained in Example 1.

[0021] Figure 2 This is a scanning electron microscope image of Ru / NiCo obtained in Example 1.

[0022] Figure 3 The Raman spectra of Ru / NiCo and NiCo obtained in Example 1 are shown.

[0023] Figure 4 A diagram showing the mass percentage of each element in the Ru / NiCo obtained in Example 1 as determined by ICP testing.

[0024] Figure 5The linear voltammetric curve of the hydrogen evolution performance test of Ru / NiCo obtained in Example 1 (1 mol / L potassium hydroxide) is shown.

[0025] Figure 6 The Ru / NiCo obtained in Example 1 is -10 mA cm -2 Stability test curve under current density.

[0026] Figure 7 The Ru / NiCo obtained in Example 1 is -1000mA cm -2 Stability test curve under current density.

[0027] Figure 8 The linear voltammetric curve of the hydrogen evolution performance test of Ru / NiMo obtained in Example 2 (1 mol / L potassium hydroxide) is shown.

[0028] Fig. 9 The linear voltammetric curve of the hydrogen evolution performance test of Ru / NiCu obtained in Example 3 (1 mol / L potassium hydroxide) is shown.

[0029] Fig.10 The linear voltammetric curve of the hydrogen evolution performance test of Ru / NiSn obtained in Example 4 (1 mol / L potassium hydroxide) is shown.

[0030] Fig.11 The linear voltammetric curve of the hydrogen evolution performance test of Ru / NiZn obtained in Example 5 (1 mol / L potassium hydroxide) is shown. DETAILED DESCRIPTION

[0031] The present invention is further described below in conjunction with specific embodiments. Example 1

[0032] A method for preparing a nickel-based electrocatalyst for alkaline high current hydrogen evolution comprises the following steps: (1) A nickel-cobalt thin film was deposited on nickel foam using a DC magnetron sputtering system. First, the target material was installed and the treated nickel foam was fixed in the sample area. During the deposition process, the working atmosphere was high-purity argon gas and the vacuum degree of the thin film gauge was 0.5 Pa. Before the formal deposition, a nickel target with a purity of 99.999% and a cobalt target with a purity of 99.999% were pre-sputtered for five minutes at 70 W in an argon atmosphere to remove the surface oxide layer. The deposition power of nickel was then adjusted to 50 W and that of cobalt to 20 W. The deposition was carried out for thirty minutes on both sides to obtain a nickel-cobalt alloy pre-catalyst (denoted as NiCo).

[0033] (2) The NiCo obtained in step (1) is immersed in a 20 mL aqueous solution containing 25 mg of ruthenium trichloride hydrate for two hours, and then 10 mL of 0.5 mol / L sodium borohydride solution is added dropwise to the ruthenium trichloride solution. The whole process is controlled within fifteen minutes. When all the sodium borohydride solution is added and no obvious bubbles are generated, it is allowed to stand for three hours to allow the system to fully react. Finally, the nickel foam is taken out, washed with deionized water and ethanol several times to wash away the ruthenium particles that are not firmly attached to the surface, and dried in an oven at 110°C for three hours to obtain a nickel-based electrocatalyst (denoted as Ru / NiCo).

[0034] The scanning electron microscope image of the NiCo alloy precatalyst prepared in Example 1 is as follows: Figure 1 As shown by Figure 1 It can be seen that the prepared NiCo alloy precatalyst is attached to the surface of nickel foam in the form of a thin film, and its cross section is a closely arranged columnar structure with a thickness of about 172.5 nm.

[0035] The scanning electron microscope image of the Ru / NiCo electrocatalyst prepared in Example 1 is as follows Figure 2 As shown by Figure 2 It can be proved that Ru particles are successfully attached to the surface of NiCo alloy film and are distributed evenly.

[0036] The Raman spectra of the NiCo and Ru / NiCo electrocatalysts prepared in Example 1 are as follows: Figure 3 As shown by Figure 3 It can be seen that the peaks of Ru / NiCo and NiCo are basically the same, at 185cm -1 and 615cm -1 The peak at 510 cm corresponds to the Co-O bond. -1 The peak at 963 cm corresponds to the Ni-O bond. -1 The weak peak at corresponds to the surface Ru-O bonds, indicating that both Ru / NiCo and NiCo surfaces are slightly oxidized.

[0037] The mass percentage of each element in the Ru / NiCo electrocatalyst prepared in Example 1 is as follows: Figure 4 As shown by Figure 4 It can be seen that the mass ratio of Ru is 2.35wt%, the mass ratio of Ni is 90.15wt%, and the mass ratio of Co is 7.49wt%.

[0038] The alkaline hydrogen evolution performance test curve of the Ru / NiCo electrocatalyst prepared in Example 1 is as follows: Figure 5 As shown by Figure 5 It can be seen that the prepared nickel-based electrocatalyst only needs 15mV and 94mV to reach -10mA cm -2 and -100mA cm -2The current density can be driven at 178mV and 234mV to 500mA cm -2 and -1000mA cm -2 of high current density.

[0039] The Ru / NiCo electrocatalyst prepared in Example 1 has a -2 The stability test curve is as follows Figure 6 As shown by Figure 6 It can be seen that the prepared nickel-based electrocatalyst can -2 The device can run stably for 100 hours at a current density of 1.

[0040] The Ru / NiCo electrocatalyst prepared in Example 1 was -2 The stability test curve below is as follows Figure 7 As shown by Figure 7 It can be seen that the prepared nickel-based electrocatalyst can be -2 It can run stably for 100 hours at a current density of 1.5 MW. This shows that it can stably drive the hydrogen evolution reaction at a high current density for a long time. Example 2

[0041] A method for preparing a nickel-based electrocatalyst for alkaline high current hydrogen evolution comprises the following steps: (1) A nickel-molybdenum thin film was deposited on nickel foam using a DC magnetron sputtering system. First, the target material was installed and the treated nickel foam was fixed in the sample area. During the deposition process, the working atmosphere was high-purity argon gas and the vacuum degree of the film gauge was 0.7 Pa. Before the formal deposition, a nickel target with a purity of 99.999% and a molybdenum target with a purity of 99.95% were pre-sputtered for five minutes at 70 W in an argon atmosphere to remove the surface oxide layer. The deposition power of nickel was then adjusted to 50 W and that of molybdenum to 20 W. The deposition was carried out for thirty minutes on both sides to obtain a nickel-molybdenum alloy pre-catalyst (denoted as NiMo).

[0042] (2) The NiMo obtained in step (1) is immersed in a 20 mL aqueous solution containing 25 mg of ruthenium trichloride hydrate for two hours, and then 10 mL of 0.5 mol / L sodium borohydride solution is added dropwise to the ruthenium trichloride solution. The whole process is controlled within fifteen minutes. When all the sodium borohydride solution is added and no obvious bubbles are generated, it is allowed to stand for three hours to allow the system to fully react. Finally, the nickel foam is taken out, washed with deionized water and ethanol several times to rinse off the ruthenium particles that are not firmly attached to the surface, and dried in an oven at 110°C for three hours to obtain a nickel-based electrocatalyst (denoted as Ru / NiMo).

[0043] The alkaline hydrogen evolution performance test curve of the Ru / NiMo electrocatalyst prepared in Example 2 is as follows: Figure 8 As shown by Figure 8 It can be seen that the prepared nickel-based electrocatalyst only needs 473mV to reach -1000mA cm -2 of high current density. Example 3

[0044] A method for preparing a nickel-based electrocatalyst for alkaline high current hydrogen evolution comprises the following steps: (1) A nickel-copper thin film was deposited on nickel foam using a DC magnetron sputtering system. First, the target material was installed and the treated nickel foam was fixed in the sample area. During the deposition process, the working atmosphere was high-purity argon gas and the vacuum degree of the thin film was 0.7 Pa. Before the formal deposition, a nickel target with a purity of 99.999% and a copper target with a purity of 99.999% were pre-sputtered for five minutes at 70 W in an argon atmosphere to remove the surface oxide layer. The deposition power of nickel was then adjusted to 50 W and that of copper to 20 W. The deposition was performed for thirty minutes on both sides to obtain a nickel-copper alloy pre-catalyst (denoted as NiCu).

[0045] (2) The NiCu obtained in step (1) is immersed in a 20 mL aqueous solution containing 25 mg of ruthenium trichloride hydrate for two hours, and then 10 mL of 0.5 mol / L sodium borohydride solution is added dropwise to the ruthenium trichloride solution. The whole process is controlled within fifteen minutes. When all the sodium borohydride solution is added and no obvious bubbles are generated, it is allowed to stand for another three hours to allow the system to fully react. Finally, the nickel foam is taken out, washed with deionized water and ethanol several times to rinse off the ruthenium particles that are not firmly attached to the surface, and dried in an oven at 110°C for three hours to obtain a nickel-based electrocatalyst (denoted as Ru / NiCu).

[0046] The alkaline hydrogen evolution performance test curve of the Ru / NiCu electrocatalyst prepared in Example 3 is as follows: Fig. 9 As shown by Fig. 9 It can be seen that the prepared nickel-based electrocatalyst only needs 399mV to reach -1000mA cm -2 of high current density. Example 4

[0047] A method for preparing a nickel-based electrocatalyst for alkaline high current hydrogen evolution comprises the following steps: (1) A nickel-tin thin film was deposited on nickel foam using a DC magnetron sputtering system. First, the target material was installed and the treated nickel foam was fixed in the sample area. During the deposition process, the working atmosphere was high-purity argon gas and the vacuum degree of the thin film was 0.7 Pa. Before the formal deposition, a nickel target with a purity of 99.999% and a tin target with a purity of 99.999% were pre-sputtered for five minutes at 70 W in an argon atmosphere to remove the surface oxide layer. The deposition power of nickel was then adjusted to 50 W and that of tin to 20 W. The deposition was carried out for thirty minutes on both sides to obtain a nickel-tin alloy pre-catalyst (denoted as NiSn).

[0048] (2) The NiSn obtained in step (1) is immersed in a 20 mL aqueous solution containing 25 mg of ruthenium trichloride hydrate for two hours, and then 10 mL of 0.5 mol / L sodium borohydride solution is added dropwise to the ruthenium trichloride solution. The whole process is controlled within fifteen minutes. When all the sodium borohydride solution is added and no obvious bubbles are generated, it is allowed to stand for three hours to allow the system to fully react. Finally, the nickel foam is taken out, washed with deionized water and ethanol several times to rinse off the ruthenium particles that are not firmly attached to the surface, and dried in an oven at 110°C for three hours to obtain a nickel-based electrocatalyst (denoted as Ru / NiSn).

[0049] The alkaline hydrogen evolution performance test curve of the Ru / NiSn electrocatalyst prepared in Example 4 is as follows: Fig.10 As shown by Fig.10 It can be seen that the prepared nickel-based electrocatalyst only needs 432mV to reach -1000mA cm -2 of high current density. Example 5

[0050] A method for preparing a nickel-based electrocatalyst for alkaline high current hydrogen evolution comprises the following steps: (1) A nickel-zinc film was deposited on nickel foam using a DC magnetron sputtering system. First, the target material was installed and the treated nickel foam was fixed in the sample area. During the deposition process, the working atmosphere was high-purity argon gas and the vacuum degree of the film was 0.8 Pa. Before the formal deposition, a nickel target with a purity of 99.999% and a zinc target with a purity of 99.999% were pre-sputtered for five minutes at 70 W in an argon atmosphere to remove the surface oxide layer. The deposition power of nickel was then adjusted to 50 W and that of zinc to 20 W. The deposition was performed on both sides for thirty minutes each to obtain a nickel-zinc alloy pre-catalyst (denoted as NiZn).

[0051] (2) The NiZn obtained in step (1) is immersed in a 20 mL aqueous solution containing 25 mg of ruthenium trichloride hydrate for two hours, and then 10 mL of 0.5 mol / L sodium borohydride solution is added dropwise to the ruthenium trichloride solution. The whole process is controlled within fifteen minutes. When all the sodium borohydride solution is added and no obvious bubbles are generated, it is allowed to stand for three hours to allow the system to fully react. Finally, the nickel foam is taken out, washed with deionized water and ethanol several times to rinse off the ruthenium particles that are not firmly attached to the surface, and dried in an oven at 110°C for three hours to obtain a nickel-based electrocatalyst (denoted as Ru / NiZn).

[0052] The alkaline hydrogen evolution performance test curve of the Ru / NiZn electrocatalyst prepared in Example 5 is as follows: Fig.11 As shown by Fig.11 It can be seen that the prepared nickel-based electrocatalyst only needs 381mV to reach -1000mA cm -2of high current density.

[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although detailed description is given with reference to the embodiments of the present invention, those skilled in the art should understand that modifications or equivalent substitutions of the technical solutions of the present invention do not depart from the spirit and scope of the technical solutions of the present invention, and should be covered by the protection scope of the claims of the present invention.

Claims

1. A nickel-based electrocatalyst, characterized in that With nickel foam as the base material, a layer of nickel-based alloy film is deposited on the surface of the nickel foam by a magnetron sputtering method, and then a nickel-based electrocatalyst is obtained by a liquid phase reduction method.

2. The method for preparing a nickel-based electrocatalyst according to claim 1, characterized in that: The following steps are involved: (1) A nickel-based alloy film was deposited on nickel foam by DC magnetron sputtering: first, the target material was installed and the treated nickel foam was fixed in the sample area. During the deposition process, the working atmosphere was argon and the pressure was selected according to different transition metals. Before the formal deposition, the nickel target and the different transition metal targets were pre-sputtered in an argon atmosphere for five minutes to remove the surface oxide layer. Then, the deposition power of nickel was adjusted to 50 W and the deposition power of other transition metals was adjusted to 20 W. The deposition was carried out for 30 minutes on both sides to obtain a nickel-based alloy pre-catalyst. (2) The nickel-based alloy precatalyst obtained in step (1) is immersed in a ruthenium trichloride solution, and then reduced with a sodium borohydride solution. The ruthenium attached to the surface of the nickel foam is then washed away with deionized water, washed with ethanol, and dried to obtain a nickel-based electrocatalyst.

3. The method for preparing a nickel-based electrocatalyst according to claim 2, characterized in that: The purity of the argon gas in step (1) is 99.999% and the flow rate is 30 sccm.

4. The method for preparing a nickel-based electrocatalyst according to claim 2, characterized in that: Step (1) The pre-sputtering power of the nickel target and the different transition metal targets is 70 W.

5. The method for preparing a nickel-based electrocatalyst according to claim 2, characterized in that: The transition metal targets in step (1) are cobalt, molybdenum, copper, tin and zinc. Except for the molybdenum target whose purity is 99.95%, the purity of the other targets is 99.999%.

6. The method for preparing a nickel-based electrocatalyst according to claim 5, characterized in that: The pressures corresponding to cobalt, molybdenum, copper, tin and zinc in step (1) are 0.5Pa, 0.7Pa, 0.7Pa, 0.7Pa and 0.8Pa respectively.

7. The method for preparing a nickel-based electrocatalyst according to claim 2, characterized in that: The size of the nickel foam in step (1) is 1*1.2cm -2 In step (2), the ruthenium trichloride solution is a 20 mL aqueous solution containing 25 mg of RuCl3•xH2O, and the immersion time is two hours.

8. The method for preparing a nickel-based electrocatalyst according to claim 2, characterized in that: The concentration of the sodium borohydride solution is 0.5 mol / L, and the volume ratio of the used ruthenium trichloride solution to the sodium borohydride solution is 2:

1.

9. The method for preparing a nickel-based electrocatalyst according to claim 2, characterized in that: The drying condition of step (2) is drying in an oven at 110°C for three hours.

10. Use of the nickel-based electrocatalyst according to claim 1 or the nickel-based electrocatalyst obtained by the preparation method according to claims 2-9 in an alkaline high current density cathode hydrogen evolution reaction.

Citation Information

Patent Citations

  • Ruthenium-doped ferronickel alloy catalyst for electrolysis water hydrogen production energy and preparation method

    CN108842160A

  • Preparation method for sodium borohydride alcoholysis hydrogen-making catalyst

    CN109317163A

  • Ruthenium-modified molybdenum-nickel nanorod composite catalyst as well as preparation method and application thereof

    CN114875442A

  • Preparation method and application of multicomponent alloy integral cathode for alkaline water electrolytic tank

    CN114941152A

  • Nickel alloy nano electrode and preparation method and application thereof

    CN118407010A